Comprehensive assessment of radiation shielding properties of novel multi-component lead boro-tellurite glasses. (May 2023) - Poojha, M.K. Komal; Vijayakumar, M.; Bassam, S.A.; Sayyed, M.I.; Marimuthu, K.; Alqahtani, Mohammed S.; El Shiekh, E.
Abstract: The present work is intended to establish the addition of the different modifier cations (Na, Li, Mg) along with different anionic combination (oxygen and fluorine) in the novel Lead boro-tellurite glass network in the point of view of radiation shielding material. The present novel lead boro-tellurite glasses have been synthesized following the melt quenching technique with three modifier elements (Na, Li, Mg) in the form of oxides as well as fluoride in the glass network. The variation in density and molar volume confirms the atomic rearrangements and FTIR spectral analysis reveals the presence of non-bridging oxygens in the prepared glasses. The optical absorption spectra confirm the changes in the bandgap due to the incorporation of modifiers into the glass network. The radiation shielding ability of the glasses were investigated by determining the transmission factor (TF) and other related parameters. The gamma photon attenuation abilities of the prepared Lead boro-tellurite glasses shows improved linear attenuation coefficient (μ), effective atomic number (Zeff ) and half value layer (HVL) when the cations are incorporated in the form of fluorides. Authors found that the TF for NaO:Pr glass at a thickness of 0.6 cm increases from 0.69 at 0.3 MeV to 0.89 at 1 MeV, and 0.94 at 5 MeV. The TF results demonstrated that adding MgO instead of Na2 O to the glasses reduces the number of photons that can penetrate the glass, enhancing the radiation-shielding properties of the glass system. Authors evaluated the effective atomic number (Zeff ) and found that the Zeff values vary between 56.55 and 57.14 at 0.015 MeV. Also, the Zeff results confirmed that adding MgO into the glasses leads to a great increase in Zeff values. Among the prepared glasses, Mg 2+ cations incorporated glass exhibits higher shielding efficacy and it may be suggested as a promising radiation shielding material. Highlights: Lead boro-tellurite glasses for Radiation shielding properties. Triple component (Na, Li, Mg) in the form of oxides and fluorides. Formation of bridging oxygen constitutes the glass to be a tightly packed structure. LAC values increases with increase in density of the prepared glasses. Among the prepared glasses Mean Free Path values are lesser for MgO:Pr glass.